Potential effects of Nigella sativa and thymoquinone on the foetal development of cyclophosphamide-treated male mice - Abdul Rahman, Suzanah; Rahmat, Nur Syamim; Lim, Sue Yee; Fong, Lau Seng; Hiew, Mark; Shah, Sayed Inayatullah; Abdul Samat, Nadia Hanis; Zainal Azman, Jaezah Adlina; Ahmad, Nur Amalina (Faculty of Biosciences and Medical Engineering, Universiti Teknologi Malaysia, 2016)
Cyclophosphamide (CPA) is an alkylating agent that is widely used as a chemotherapy drug among male of reproductive age. The drug causes chromosomal aberration (CA) in sperm which can decrease fertility and contribute to foetal abnormality. Many studies in animal have showed that foetal abnormalities induced by cyclophosphamide can be ameliorated using antioxidants. Traditional medicine such as Nigella sativa (NS) and its active compound, Thymoquinone (TQ), are widely used for their antioxidant activities. However, their antioxidative effects on teratogenicity in animal models remain unknown. Therefore, this study aimed to investigate the possible potential effects of NS and TQ on foetal development after paternal exposure to cyclophosphamide. Male ICR mice (n=3) were assigned randomly into 6 groups: (a) Vehicle control, (b) 200 mg/kg CPA, (c) 10 mg/kg NSE, (d) 10 mg/kg TQ, (e) 200 mg/kg CPA & 10 mg/kg NSE and (d) 200 mg/kg CPA & 10 mg/kg TQ. Male mice were then mated with the same strain of untreated female mice after 32 days. The foetuses were scanned using ultrasound modality to obtain their images and measurement of gestational sac size, biparietal diameter (BPD), crown-rump length (CRL) and heart rate activity. The foetuses were also analyzed for their morphological and skeletal malformations. The positive control and combination group of CPA and TQ showed no pregnancies whilst exposure to CPA supplemented with NS increased fertility rate. Between supplement groups alone, TQ improved pregnancy by the record of the highest number foetuses collected and number of impregnated female mice as compared to NS exposure alone. The measurements of CRL and BPD of foetuses in mice treated with TQ alone were 9.10±0.89 mm and 5.48±0.54mm respectively compared to 10.71±1.35 mm and 6.04±0.52 mm observed in control group. The measurements of BPD and CRL were significantly reduced compared to negative control group. This study indicated that NS could be a protective antioxidant against CPA-induced infertility while TQ alone may have the potential to promote and improve pregnancy success.